2018
DOI: 10.14202/vetworld.2018.778-781
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of local and exotic sheep breeds in Jordan using microsatellites markers

Abstract: Aim:This study was conducted to study the genetic and population structure of local (Awassi) and exotic (Romanov, Charollais, Assaf, Awassi, and Suffolk) sheep breeds in Jordan using eight microsatellite markers.Materials and Methods:A total of 125 sheep were used (25 from each breed) in the study. The number of alleles (A), the mean values of observed (Ho) and expected (He) heterozygosity, polymorphism information content (PIC), fixation index as a measure of heterozygote deficiency or excess, and Hardy–Weinb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
4
7
1
Order By: Relevance
“…Estimates were also comparable with that of the Kajali sheep, that belong to the NWASA region 21 and four sheep populations of the SP region; Madras Red, Mecheri, and Pattanam 27 and Tiruchi Black 28 . The genetic variability observed in this study was higher than those reported in Jordan sheep 29 , and sheep breeds of the neighboring country, Pakistan 30 . However, it was comparable to the values reported across the world, for sheep 31,32 .…”
Section: Discussioncontrasting
confidence: 82%
“…Estimates were also comparable with that of the Kajali sheep, that belong to the NWASA region 21 and four sheep populations of the SP region; Madras Red, Mecheri, and Pattanam 27 and Tiruchi Black 28 . The genetic variability observed in this study was higher than those reported in Jordan sheep 29 , and sheep breeds of the neighboring country, Pakistan 30 . However, it was comparable to the values reported across the world, for sheep 31,32 .…”
Section: Discussioncontrasting
confidence: 82%
“…Similarly, our analysis of the data showed that the greatest genetic diversity was detected in the Edilbay-1 sheep breed, with a mean value of alleles of 8.333 ± 0.644, and these indicators did not differ much among the remaining populations (Table 2). The allele diversity for Edilbay-1 was similar to that of Arabian sheep studied with 12 microsatellite loci (Ahmed et al, 2018) but much higher than that reported for Jordan sheep breeds (Khaleel et al, 2018). The lowest genetic diversity among the breeds studied was expressed in Kazakh Arkhar-Merino, with an average value of seven alleles.…”
Section: Discussionsupporting
confidence: 68%
“…Except for CA, GG, CH, OU, RO, and SF, the expected heterozygosity was lower than the observed ( Table 2). The level of heterozygosity within breeds was in agreement with previous studies in different sheep breeds (Peter et al, 2007;Jyotsana et al, 2010;Jawasreh et al, 2018;Bravo et al, 2019). In general, the results showed that the heterozygosity across and within breeds was sufficient concerning the potential loss of genetic diversity in the next generations.…”
Section: Resultssupporting
confidence: 90%